Practical Considerations When Navigating Maritime Disputes: Pre-Award Security Through Emergency Arbitration - Alberti, Christian P (Journal of maritime law and commerce, 2019)
The advantages attributed to arbitrating transnational maritime disputes outweigh those one may find in local courts. For one, arbitral awards are "reachable on her arrival" in currently 159 countries that are signatories to the 1958 Convention on the Recognition and Enforcement of Foreign Arbitral Awards ("New York Convention").1 But all too often do winning parties find themselves in a precarious situation by having spent good money to obtain an otherwise perfectly enforceable award, only to then find out that there is little left, if anything, to reach into. As such, return on investment considerations need to be taken seriously before starting an arbitration campaign. The following sections will focus on pre-award security through emergency arbitration and how proper application may reduce, if not eliminate, the risk of investing funds into a lost cause. This article will then also briefly address the status quo on enforcement concerns raised in the context of emergency arbitration decisions.